2012
DOI: 10.1002/ange.201202750
|View full text |Cite
|
Sign up to set email alerts
|

Edelmetalle in Polyoxometallaten

Abstract: Polyoxometallate, die Edelmetallionen wie Ruthenium, Osmium, Rhodium, Palladium, Platin, Silber und Gold enthalten, bilden eine strukturell reichhaltige Klasse von Verbindungen. Hierzu gehören sowohl klassische Heteropolyanionen (Vanadate, Molybdate, Wolframate), in denen die Edelmetalle als Heteroatome vorliegen, als auch die erst kürzlich entdeckte Klasse der Polyoxometallate mit Edelmetallen als “Addenda”‐Atomen. Der Schwerpunkt dieses Aufsatzes liegt auf Komplexen, die in Lösung als diskrete Moleküle vorli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 234 publications
(165 reference statements)
0
13
0
Order By: Relevance
“…Single-crystal X-ray analysis on Na-Au 4 Pd 8 revealed that the title polyanion Au 4 Pd 8 has a structure which is very similar to that of the cuboid-shaped polyoxopalladates MPd 12 X 8 , [11] comprising a central, cubic NaO 8 moiety (Na···O 2.37(3) ) surrounded by 12 noble metal centers forming a cuboctahedron, which is capped by eight tetrahedral arsenate groups. The high crystal symmetry of Na-Au 4 Pd 8 did not allow for determining the exact positions of the Au III and Pd II centers, as the entire M 12 cage (due to the Fm3 m space group) was modeled by only one unique electron density peak, but the Au/Pd ratio of 4:8 was clearly established (see the Supporting Information for details), and supported by elemental analysis (see below).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Single-crystal X-ray analysis on Na-Au 4 Pd 8 revealed that the title polyanion Au 4 Pd 8 has a structure which is very similar to that of the cuboid-shaped polyoxopalladates MPd 12 X 8 , [11] comprising a central, cubic NaO 8 moiety (Na···O 2.37(3) ) surrounded by 12 noble metal centers forming a cuboctahedron, which is capped by eight tetrahedral arsenate groups. The high crystal symmetry of Na-Au 4 Pd 8 did not allow for determining the exact positions of the Au III and Pd II centers, as the entire M 12 cage (due to the Fm3 m space group) was modeled by only one unique electron density peak, but the Au/Pd ratio of 4:8 was clearly established (see the Supporting Information for details), and supported by elemental analysis (see below).…”
mentioning
confidence: 97%
“…[8] To date more than 40 polyoxopalladates(II) of different shape, size, and composition have been prepared following this simple synthetic strategy, by using various external heterogroups RXO 3 nÀ (X = P V , As V , Se IV , V V ; and R= O, Ph, lone pair) and many different central metal ion guests. [9][10][11] A similar approach was also successfully applied for the condensation of [Au(OH) 4 [12] Interestingly, for the arsenate derivative Au 4 As 4 two polyanions are linked in the solid state via a belt of five Na + countercations into a cuboid-shaped assembly Na 5 -(Au 4 As 4 ) 2 , [12a] with a structure resembling the polyoxopalladate family [MPd II 12 O 8 (RXO 3 ) 8 ] nÀ (MPd 12 X 8 ). [11] This inspired us to try and replace the four peripheral Na + ions in such Na 5 (Au 4 As 4 ) 2 assembly by Pd II ions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In polyoxotungstates, architectural control can be achieved at the fragment level by carefully selecting the heteroanion templates. [7][8][9][10][11] However, discriminating the selfassembly, aggregation, and isolation of nanoscale POM species as a function of time, and while under supramolecular control, were especially difficult until now. [6] In this way, it is possible to generate a diverse library of nucleophilic POM "secondary building units" (SBUs) which can serve as well-defined precursors in the formation of larger assemblies, which can be intricately controlled by the use of the heteroanion as well as linking coordinating cations.…”
mentioning
confidence: 99%
“…In particular, we have been using anions such as (SeO 3 ) 2À and (TeO 3 ) 2À , which can exert a powerful structure-directing effect as a result of the lone pair of the heteroanion, [5] itself templating massive structures. [7][8][9][10][11] However, discriminating the selfassembly, aggregation, and isolation of nanoscale POM species as a function of time, and while under supramolecular control, were especially difficult until now. [7][8][9][10][11] However, discriminating the selfassembly, aggregation, and isolation of nanoscale POM species as a function of time, and while under supramolecular control, were especially difficult until now.…”
mentioning
confidence: 99%